An anthropology of the Qur'an - Achrati, Ahmed (Routledge studies in religion, 2021)
Part I. Introduction -- 1. Religion, the Holy and the Sacred: An Anthropological Perspective -- 2. Al-Quddūs (The Holy) and Transcendental Écart in the Qur'ān -- 3. Ontological Distinction of the Holy and the Sacred in the Qur'ān -- 4. Transcendence and Divine Freedom in the Qur'ān -- 5 Tawḥīd, God, the Qur'ān, and Being -- 6. Al-Quddūs and Divine Otherness -- 7. Tawḥīdic Discourses and the Inversion of al-Quddūs -- 8. The Qur'ān and the Sublimation of the Sunna -- 9. The Qur'ān, Muḥammad and the Disclosure of the Holy --10. The Qur'ān, the Sunna, and Authority in Modern Islam -- Part II. 11. Gender: The Tawḥīdic Sexual Morality --12. ḤILM: The Forgotten Ethics of Islam -- 13. The Qur'ān and Islamic Art -- 14. Ribā (Usury): Economic Excess and Excessive Morality.